2014
DOI: 10.1183/09031936.00084514
|View full text |Cite
|
Sign up to set email alerts
|

Pedometers to enhance physical activity in COPD: a randomised controlled trial

Abstract: Physical inactivity is a cardinal feature of chronic obstructive pulmonary disease (COPD), and is associated with increased morbidity and mortality. Pedometers, which have been used in healthy populations, might also increase physical activity in patients with COPD.COPD patients taking part in a 3-month individualised programme to promote an increase in their daily physical activity were randomised to either a standard programme of physical activity encouragement alone, or a pedometer-based programme. Assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
232
2
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(249 citation statements)
references
References 41 publications
7
232
2
8
Order By: Relevance
“…Adherence with the step counter was excellent, in line with previous studies [4,7,10,11]. By contrast, adherence with the smartphone tasks was lower.…”
Section: Fidelitysupporting
confidence: 76%
See 1 more Smart Citation
“…Adherence with the step counter was excellent, in line with previous studies [4,7,10,11]. By contrast, adherence with the smartphone tasks was lower.…”
Section: Fidelitysupporting
confidence: 76%
“…While the adherence with step counters is known to be relatively good in short-term coaching trials involving patients with COPD [4,10,11], adherence with smartphone applications in coaching trials has been less intensively studied. 2) Patient satisfaction and perceived usefulness of the different components of the PA telecoaching intervention.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to existing research [6], our results provide evidence to consider in the current COPD guidelines/strategies that COPD patients in general should be encouraged to perform an extra quantity of low-intensity physical activity during their daily life. Furthermore, the data suggest that research aiming to assess the effectiveness of physical activity interventions should consider several physical activity outcomes, including the proportion of individuals meeting certain physical activity goals [34], extra steps per day [35] and the changes, if any, in average intensity.…”
Section: Clinical Implications Of Resultsmentioning
confidence: 99%
“…DE BLOK et al [77] found a 1000-step difference in increasing daily activity by adding a physical activity counselling programme to a 9-week PR programme, in comparison with a control group. More recently, the effects of pedometer-based programmes in patients with COPD have been investigated in more detail and increases in daily physical activity ranging 600-3000 steps have been reported in comparison with control groups [98][99][100][101][102][103]. Two studies reported a pedometer-based intervention, during which patients were coached by telephone [101,102].…”
Section: Modification Of Patient Behaviourmentioning
confidence: 99%